The Illusion of Being Located in Dynamic Virtual Environments. Can Eye Movement Parameters Predict Spatial Presence? - Bartholomäus Wissmath; Daniel Stricker; David Weibel; Eva Siegenthaler; Fred W. Mast (Bern Open Publishing, 2010)
Attention allocation towards the mediated environment is assumed to be a necessary precondition to feel localized in a virtual world. In presence research, however, the potential of eye movement research has not been fully exploited so far. In this study, participants (N=44) rode on a virtual roller coaster simulation. We compare participants scoring high versus low on presence. During the ride, the eye movements and subjective ex post presence judgments were assessed. We found high sensations of presence to be associated with fewer fixations and a tendency towards longer fixation durations. In contrast to the immersive tendency trait, eye movement parameters can predict presence.